THE IMPACT OF HEALTH EDUCATION ON COMPLEMENTARY FOODS (MPASI)ON THE APPROPRIATENESS OF PROVIDING COMPLEMENTARY FOODS TO MOTHERS OF TODDLERS IN WRINGIN VILLAGE, WRINGIN DISTRICT - Dian Rahmawati; Iis Hanifah; Suhartin (The Shine Cahaya Dunia Kebidanan, 2026)
Background: Provision of appropriate complementary foods (MPASI) plays a crucial role in meeting children's nutritional needs during early growth. Inappropriate complementary feeding (MPASI) in terms of timing, texture, frequency, and menu variety can increase the risk of nutritional problems such as stunting and micronutrient deficiencies. A lack of maternal knowledge is often a major factor behind inappropriate complementary feeding practices. The purpose of this study was to analyze the effect of health education about MPASI on the appropriateness of MPASI provision among mothers of toddlers in Wringin Village, Wringin District. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. The population included all 54 mothers of children aged 6-23 months in Wringin Village, Wringin District. The sample size was 47 mothers of children aged 6-23 months in Wringin Village, Wringin District. Results: The Wilcoxon statistical test results indicate a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is smaller than α, H₀ is rejected and H₁ is accepted. This indicates that health education about complementary feeding (MPASI) has an effect on the accuracy of providing complementary feeding to mothers of toddlers in Wringin Village. Conclusion: The results of this study indicate that health education about complementary feeding (MPASI) has an effect on the accuracy of providing complementary feeding to mothers of toddlers in Wringin Village.